(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The provision of services of good quality and quantity is vital to improve and sustain human life and living standards of the population of any community in Cameroon in general and Kumba councils in particular. This service ranges from health, education, sports sanitation, electricity, drinking water, toilets to roads. Generally, the type of public goods and services and the way services are delivered by local government are frequently changing in the context of delivery. The Changes come from technological innovations, scientific innovations, availability of resources and changes emerging both internally and externally, though several attempt has been made to enhance service delivery of local government. The creation of city councils to ease service delivery in the municipality, creation of the ministry of public contract, putting in place a contract board through continuous technical and financial assistance in the Kumba councils. Despite this measures, service delivery in the Kumba municipalities have not improved. Thus the main objective is to examine the extent to which the establishment and management of local/municipal government enterprises affects the provision of services within the Kumba Councils A hybrid of qualitative and quantitative approaches was employed and a descriptive design adopted for the study, constituting inhabitants and mayors of the three councils were selected using a sampling technique. Primary data was then collected from these participants using a questionnaire and interviews. Though several attempts have been made to enhance service delivery of local government through continuous technical and financial assistance, it is realised that in most cases, the local people where totally excluded from getting public services due to a number of factors ranging from political interference, corruption lack of competition, poor public private partnership, inadequate financial resources. Therefore, this also focuses on how councils will overcome these obstacles of service delivery. The major findings of this study is that, local government service in the Kumba municipalities implemented several strategies and innovations as developing partnerships with the private sectors and also enhance the public partnership in the service delivery process, but still failed to ensure accountability, efficiency and transparency in service delivery. It is realised that, some of hindrances to the realisation of accountability, efficiency and transparency of local government service provision is that, the councils lack autonomy to bring about a level of efficiency and accountability in their management and provision of services. this includes shortage of competence human resources, political interference, unclear power and functions to provide services, inadequate financial resources and unqualified staffs? The key recommendations is that local governments in Cameroon need adequate autonomy that can assist them to be efficient in service delivery.